Voltage-driven motion of nitrogen ions: a new paradigm for magneto-ionics - de Rojas, Julius; Quintana, Alberto; Lopeandía, Aitor; Salguero, Joaquín; Muñiz, Beatriz; Ibrahim, Fatima; Chshiev, Mairbek; Nicolenco, Aliona; Liedke, Maciej O.; Butterling, Maik; Wagner, Andreas; Sireus, Veronica; et al. (Nature communications, 2020)
Magneto-ionics, understood as voltage-driven ion transport in magnetic materials, has largely relied on controlled migration of oxygen ions. Here, we demonstrate room-temperature voltage-driven nitrogen transport ( i.e ., nitrogen magneto-ionics) by electrolyte-gating of a CoN film. Nitrogen magneto-ionics in CoN is compared to oxygen magneto-ionics in Co 3 O 4 . Both materials are nanocrystalline (face-centered cubic structure) and show reversible voltage-driven ON-OFF ferromagnetism. In contrast to oxygen, nitrogen transport occurs uniformly creating a plane-wave-like migration front, without assistance of diffusion channels. Remarkably, nitrogen magneto-ionics requires lower threshold voltages and exhibits enhanced rates and cyclability. This is due to the lower activation energy for ion diffusion and the lower electronegativity of nitrogen compared to oxygen. These results may open new avenues in applications such as brain-inspired computing or iontronics in general. In magneto-ionics, ion migration through the material is used to change the materials magnetic properties. Typically oxygen is used as the mobile ion. In this manuscript, the authors demonstrate controlled migration of nitrogen in a CoN film, expanding the possibilities of magneto-ionics.